Abnormalities of Thymic Stroma may Contribute to Immune Dysregulation in Murine Models of Leaky Severe Combined Immunodeficiency - Rucci, Francesca; Poliani, Pietro L.; Caraffi, Stefano; Paganini, Tiziana; Fontana, Elena; Giliani, Silvia; Alt, Frederick W.; Notarangelo, Luigi D. (Frontiers in Immunology, 2011)
Lymphostromal cross-talk in the thymus is essential to allow generation of a diversified repertoire of T lymphocytes and to prevent autoimmunity by self-reactive T cells. Hypomorphic mutations in genes that control T cell development have been associated with immunodeficiency and immune dysregulation both in humans and in mice. We have studied T cell development and thymic stroma architecture and maturation in two mouse models of leaky SCID, carrying hypomorphic mutations in Rag1 and Lig4 genes. Defective T cell development was associated with abnormalities of thymic architecture that predominantly affect the thymic medulla, with reduction of the pool of mature medullary thymic epithelial cells (mTECs). While the ability of mTECs to express Aire is preserved in mutant mice, the frequency of mature mTECs expressing Aire and tissue-specific antigens (TSAs) is severely reduced. Similarly, the ability of CD4+ T cells to differentiate into Foxp3+ natural regulatory T cells is preserved in Rag1 and Lig4 mutant mice, but their number is greatly reduced. These data indicate that hypomorphic defects in T cell development may cause defective lymphostromal cross-talk and impinge on thymic stromal cells maturation, and thus favor immune dysregulation.